Analyzing Architectural Drawing in the Works of Four Contemporary Chinese and Japanese Architects: A Multi-Dimensional Approach - Lei Tan; Tomoyuki Tanaka; Jiahao Liu (Architecture)
In the image era, architectural drawing gradually evolved from being a part of traditional architectural design to an artistic form with independent aesthetic value. However, a systematic evaluation method for this unique art form is still lacking. This study analyzes the works of four Chinese and Japanese architects, focusing on the functionality and artistry of architectural drawings. Combining iconography, semiotic analysis, and theories from visual culture studies, it explores the visual language and cultural significance embedded in architectural drawings from a new perspective and attempts to establish an evaluation framework. The analysis of visual symbols, cultural codes, and social contexts reveals how architects convey architectural concepts, historical memories, and urban landscapes through their drawings. This study finds that architectural drawings not only convey architectural information but also integrate cultural narratives and artistic expression, serving as an important intersection between architecture and other disciplines. Although interpretations may vary across cultural contexts, the semiotic approach offers a relatively objective evaluation system. This research helps architects, artists, and educators better understand the role of architectural drawing and promotes its application in architectural design, artistic creation, and education.